2007
DOI: 10.1186/gb-2007-8-10-r227
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional profiling reveals barcode-like toxicogenomic responses in the zebrafish embryo

Abstract: (http://creativecommons.org/licenses/by/2.0), which permits unrestricted use, distribution, and reproduction in any medium, provided the original work is properly cited Zebrafish toxicogenomic responses

Microarray profiling of zebrafish embryos exposed to a range of environmental toxicants revealed distinct expression profiles for each of the toxicants tested.

Abstract Background: Early life stages are generally most sensitive to toxic effects. Our knowledge on the action of manmade chemicals on the dev…
Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
106
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 177 publications
(117 citation statements)
references
References 200 publications
9
106
2
Order By: Relevance
“…Other studies also support the observation that exposure to mercury results in tail deformities in ZFEs [57,58,62]. The study by Yang et al [57] suggests that methyl mercury specifically impairs tail development in part through activation of matrix metalloproteases 9 and 13, which are active in tissue remodelling.…”
Section: Methylmentioning
confidence: 71%
See 1 more Smart Citation
“…Other studies also support the observation that exposure to mercury results in tail deformities in ZFEs [57,58,62]. The study by Yang et al [57] suggests that methyl mercury specifically impairs tail development in part through activation of matrix metalloproteases 9 and 13, which are active in tissue remodelling.…”
Section: Methylmentioning
confidence: 71%
“…Low concentrations of methyl mercury also have adverse affects on ZFE development [45,[55][56][57]. Similar studies examined the use of ZFEs specifically to assess environmental water contamination Yang et al [58] observations that ZFEs are highly sensitive to adverse effects of exposure to mercury and the Lahnsteiner [59] study also reported that the first 24 h of ZFE development was the most sensitive period for exposure to various environmental contaminants, including HgCl 2 .…”
Section: Methylmentioning
confidence: 99%
“…This robustness indicator allows reducing data dimensionality to a manageable set of variables that can be used in environmental assessment. These patterns of gene expression (Bfingerprints,^Bbarcodes^) could be used as biomarkers identifying relevant toxicants (Aardema and MacGregor 2002;Yang et al 2007;Piña and Barata 2011). With robust indicator genes, the full potential of transcriptomics can be used.…”
Section: Discussionmentioning
confidence: 99%
“…on zebrafish (Danio rerio) (Hollert et al 2003;Höss et al 2010;Feiler et al 2013). Zebrafish embryos have become a useful model organism in ecotoxicology and ecotoxicogenomics (Yang et al 2007;Strähle et al 2012;Busquet et al 2014;Schiwy et al 2014). Recent research focused on linking gene expression analysis to current assessment methods for zebrafish embryos making it possible to investigate mechanism-specific toxicity at molecular level (Keiter et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Toxicogenomics has been selected as an experimental approach as it enables unbiased, global profiling of the molecular biological response space (Richard, 2006;Edwards and Preston, 2008), without preselection of response parameters. For single chemicals, it has been shown that exposure results in chemical-specific, gene expression profiles (Hamadeh et al, 2002;Yang et al, 2007;Kiyosawa et al, 2010;Janssens et al, 2011;Piña and Barata, 2011;Meganathan et al, 2012;Theunissen et al, 2012). The hypothesis tested in the present study is whether specific MoAs have common gene expression profiles that can be used to classify compounds and whether compounds with multiple MoAs can be classified and distinguished from those with only one MoA.…”
Section: Introductionmentioning
confidence: 93%